The pro- and anti-tumor role of ILC2s. (February 2019) - Trabanelli, Sara; Chevalier, Mathieu F.; Derré, Laurent; Jandus, Camilla
Abstract: Group 2 innate lymphoid cells (ILC2s) are critical for the initiation of type 2 inflammatory diseases. However, ILC2s are also involved in the establishment of the immune microenvironment during tumor development, growth and metastasization. In this context, ILC2s have been shown to be either tumor-suppressive or tumor-promoting according to the tumor type, the cytokine secreted and the other immune cells that are, in turn, recruited and/or activated.